Evaluation Tv- Image Quality for Different Cable Signal Transmission Resistance Based on Contrast Edge Algorithm - Dr. Raghad Abdul Al-Aali (College of Education for Women, 2019)
Some degree of noise is always present in any electronic device that transmits or receives a signal . For televisions, this signal i has been to s the broadcast data transmitted over cable-or received at the antenna; for digital cameras, the signal is the light which hits the camera sensor. At any case, noise is unavoidable. In this paper, an electronic noise has been generate on TV-satellite images by using variable resistors connected to the transmitting cable . The contrast of edges has been determined. This method has been applied by capturing images from TV-satellite images (Al-arabiya channel) channel with different resistors. The results show that when increasing resistance always produced higher noise for a television image .